The accuracy of different calculation methods when identifying handgrip strength asymmetry among middle-aged and older Chinese adults. - Yilin Wang; Jing Wang; Binyou Wang; Jing Fu; Xiaoyan Chen (PLoS ONE, 2024)
At present, there is no uniform standard mean of identifying handgrip strength (HGS) asymmetry based on maximum or average HGS values. Therefore, this study aimed to explore the accuracy of different calculation methods in the evaluation of HGS asymmetry. Using the maximum reading of two trials from both hands (Method A) as the reference standard, the accuracy of the HGS asymmetry identified by the average value of two trials of both hands (Method B) was determined by using various indicators, including specificity, sensitivity, the area under the receiver operating characteristic curve (AUC), positive, and negative predictive values. Overall, 12,163 individuals were included in this study, of whom 47.61% (5791/12,163) were male. The percentages of individuals with HGS asymmetry differed as a function of age and sex when using these two different methods. When employing Method A, 38.52%, 41.57%, and 44.57% of males 45 ≤ age<60, 60 ≤ age<80, and ≥ 80 years of age exhibited HGS asymmetry as compared to 40.78%, 39%, and 39.63% of females. Using Method B, the corresponding proportions were 41.69%, 42.5%, and 40% in males and 42.01%, 41.18%, and 40.55% in females, respectively. When compared to Method A, Method B was found to be effective in identifying HGS asymmetry, with AUC values ranging from 0.844 to 0.877. However, there was only moderate agreement between the two methods in assessing HGS asymmetry. Specifically, the Kappa values for the two Methods were 0.692, 0.694, and 0.766 in males aged 45 to 60, 60 to 80, and 80 years and above, respectively. For females, the Kappa values were 0.674, 0.661, and 0.751, respectively. These results demonstrated that the maximal or average HGS values from two trials using both hands has a significant impact on the consequent identification of HGS asymmetry.